Brain Computer Interface issues on hand movement - Prasant Kumar Pattnaik; Jay Sarraf (Journal of King Saud University: Computer and Information Sciences)
This paper focuses on the Brain Computer Interface (BCI) application and its issues. Further the attempt was made to implement left and right hand movement classification after removal of the artifacts in the acquired signals of the various hand movements.